Collecting The Globe : The Salem East India Marine Society Museum - Schwartz, George H. (Public History in Historical Perspective, 2020)
The East India Marine Society Museum was one of the most influential collecting institutions in nineteenth-century America. From 1799 to 1867, when Salem, Massachusetts, was a premier American port and launching pad for international trade, the museum's collection developed at a nexus of global exchange, with donations of artwork, crafts, and flora and fauna pouring in from distant ports of call. At a time when the country was filled with Barnum-esque exhibitions, visitors to this museum could circumnavigate the globe and gain an understanding of the world and their place within it.0'Collecting the Globe' presents the first in-depth exploration of the East India Marine Society Museum, the precursor to the internationally acclaimed Peabody Essex Museum. Offering fresh perspectives on museums in the United States before the Civil War and how they helped shape an American identity, George H. Schwartz explores the practices of collecting, exhibiting, and interpreting a diversity of international objects and art in the early United States.